A Comparative Study of Perioperative Blood Loss in Monopolar Versus Bipolar Transurethral Resection of the Prostate: Quasi Experimental Study: Blood Loss in Transurethral Resection of the Prostate - Ali, Rao Nouman; Irfan, Muhammad; Mahmood, Athar; Ahmad, Muhammad Zahid; Irfan, Sohaib; Shahzad, Shafqat (Pakistan Journal of Health Sciences, 2024)
Transurethral Resection of the Prostate (TURP) is frequently performed for Benign Prostatic Hyperplasia (BPH), and the choice between monopolar and bipolar diathermy influences blood loss. Minimizing blood loss is crucial for reducing complications and improving recovery, with bipolar diathermy generally offering better hemostasis than monopolar diathermy. Objective: To compare perioperative blood loss in monopolar versus bipolar transurethral resection for benign prostatic hyperplasia. Methods: Quasi experimental study was conducted at the Department of Urology and Renal Transplantation, DHQ Hospital Gujranwala, from December 11, 2018, to June 11, 2019. Patients were assigned to either Group A, which received monopolar diathermy, or Group B, which received bipolar diathermy, using convenience sampling technique. Each group comprised 40 patients. Hematocrit levels were assessed 24 hours’ post-surgery; hematocrit, the proportion of blood volume occupied by red blood cells, serves as an indirect measure of blood loss. Blood loss during surgery was estimated by comparing pre-operative and post-operative hematocrit readings, and the data were analyzed using SPSS version 23. Results: Perioperative blood loss was significantly higher in patients who underwent monopolar diathermy compared to those treated with bipolar diathermy (monopolar: 325.22 ml vs. bipolar: 240.0 ml, p-value = 0.0001). Similar findings were observed when stratifying by age and prostate size, indicating that bipolar TURP consistently resulted in less perioperative blood loss. Conclusions: A significant reduction in perioperative blood loss with bipolar TURP compared to monopolar TURP in BPH patients. Reduction is clinically relevant, as it may lead to lower morbidity and improved recovery times.